Incorporation of glycogenin into a hepatic proteoglycogen after oral glucose administration - (:unkn) unknown (My University, 1994)
Glycogenin is a 37-kDa protein upon which new glycogen molecules are considered to be constructed. Therefore, we were interested in determining its role in liver glycogen synthesis following glucose administration. Twenty-four-hour fasted rats were given 4 g/kg glucose orally. Glycogenin and synthase R activities and glycogen were determined over the subsequent 24 h. In fasted rats given just water, glycogenin activity was present and did not change over the subsequent 24 h. Following glucose, glycogenin activity also was not different for 1 h, i.e. the glycogenin was not incorporated into glycogen even though the glycogen concentration had increased. Subsequently, the glycogenin activity became unmeasurable. Presumably, the glycogenin was incorporated into a proteoglycan product since after amylase treatment, glycogenin activity was again present and was quantitatively unchanged. Free glycogenin activity remained unmeasurable until after 12 h. At this time, glycogen began to decrease, and, by 15 h, free glycogenin activity again appeared. The results indicate that in fasted rats, essentially all of the glycogenin was free. Following administration of oral glucose, glycogenin was incorporated into a proteoglycan product but only 60 min after glycogen synthesis had begun. Free glycogenin did not reappear until the 15(th) h after glucose was given and after the glycogen concentration had decreased by ~60%.